AN EMPIRICAL ANALYSIS OF IPOS UNDER-PRICING IN CHINESE PHARMACEUTICAL INDUSTRY DURING 2000 TO 2010 - Shen, Tingting (2010)
This paper aims to explore factors causing the IPOs pricing puzzle in Chinese pharmaceutical industry. The main theories used are the Signalling Theory, Information Asymmetric Theory and Ex ante theory. The 88 IPOs dataset are gathered from pharmaceutical A-share IPOs during the period of 2000 to 2010. The results demonstrate that under-pricing is a signal of firm quality by variable Offering Price, and as a result of information asymmetric by dummy variable Hot Market. Industrial specific variables like venture capital reputation and percentage of share held by venture capital are demonstrated to have significant impacts on initial return of IPOs. However, the results show that there is no big difference of IPOs initial return among four sub-industries.